Carragena como eliciadora em trigo e sua ação na biossíntese de desoxinivalenol por Fusarium graminearum - Ducatti, Rafael Dal Bosco (2021)
Wheat corresponds to the most important staple food for human consumption and one of the first species to have been domesticated. Although highly important, wheat faces major obstacles and losses due to the incidence of pathogenic fungi that, in addition to causing losses in productivity, end up reducing the bromatological quality of kernels and increasing the incidence and accumulation of mycotoxins in harvested kernels, causing health problems both to human and animal health. Therefore, this work aimed to use the elicitors carrageenan and Acibenzolar-S-Methyl (ASM) in order to strengthen plant defense and indirectly reduce fungal metabolism in order to reduce the synthesis and accumulation of DON in harvested kernels and improve the agronomic parameters of the crop. The experiments were carried out in the experimental area of EPAGRI – Chapecó – SC in 2020 with the wheat cultivars TBIO Audaz and TBIO Noble. The experiment was developed under a random block design with six treatments (negative control, positive control (only fungicides) and fungicides associated with ASM and 3 doses of carrageenan (Algomel PUSH 0.5; 1.0 and 1.5 L ha-1)) and four replicates. The elicitors were applied at the beginning of the elongation stage combined with the fungicide. The variables analyzed in this study were based on morphological (plant height and leaf area), physiological (SPAD, Gs, E, A, Ci, EiC and WUE), phytosanitary (incidence of powdery mildew, brown spot, yellow spot , rust and FHB), productive (productivity, PH and PMS), biochemical (CAT, SOD and PAL activity) and qualitative (bromatological and mycotoxicological quality) parameters of the crop. Due to the great water stress that affected the experimental area in 2020 associated with the time of application of the elicitors (after the incidence of stress) the effects of carrageenan and ASM were suppressed. Even so, the elicitors proved to be excellent allies to reduce the incidence of powdery mildew in both cultivars and to increase the CAT activity in the cultivar TBIO Noble. However, with the exception of leaf diseases and CAT activity (TBIO Noble), no significant differences were observed in relation to the other parameters analyzed in this work. The need and dependence on the use of fungicides in wheat fields to obtain healthier plants and higher yields is evident. The elicitors had an effect of basically two to three weeks on plants.